Software product innovation in agile usability teams: an analytical framework of social capital, network governance, and usability knowledge management. (1st January 2012) - Barksdale, Jeremy T.; McCrickard, D. Scott
As the practice of software engineering matures, project teams are leveraging the expertise of those with a background in other domains such as usability. This paper proposes a model and agenda for understanding and improving social interaction on agile usability software teams. We argue that social interaction on multidisciplinary agile usability teams, as a means to integrating the software development and usability domains, impacts how usability knowledge is managed, and thus, software product innovation. This work contributes: 1 a background, analysis, and discussion of the various agile usability integration strategies to-date 2 a model for investigating the social interaction in agile usability teams 3 a research, practice, and policy agenda for future work toward improving the social interaction in multidisciplinary agile usability software teams.